5.1 MILD REDUCTION OF GLOMERULAR FILTRATION RATE IS ASSOCIATED WITH INCREASED SYSTEMIC VASCULAR RESISTANCE INDEPENDENT OF CHANGES IN CARDIAC AUTONOMIC TONE - Ilkka Porsti; Kati Vaaraniemi; Pauliina Kangas; Antti Tikkakoski; Jenni Koskela; Anna Tahvanainen; Arttu Eraranta; Jukka Mustonen (Artery Research, 2016)
Objective: Our aim was to evaluate the influence of mild impairment in kidney function on hemodynamics and cardiac autonomic tone. Methods: We studied 561 (50% male) normotensive and hypertensive subjects without kidney or other cardiovascular diseases or antihypertensive treatment. Supine and upright hemodynamics were recorded using continuous pulse wave analysis, whole body impedance cardiography and heart rate variability analysis. Estimated glomerular filtration rate (eGFR) was calculated using the CKD-EPI cystatin C equation. Results: Mean eGFR was 99 (range 53–152) ml/min/1.73 m2 and one third of the patients had values below 90. After adjustments for age, sex, body mass index and low density lipoprotein cholesterol level, regression analysis indicated significant associations between lower eGFR and higher systolic (p<0.001) and diastolic blood pressure (p<0.001) and systemic vascular resistance (p=0.001) regardless of body position. Lower eGFR was associated with higher low frequency to high frequency ratio of heart rate variability in supine but not in upright position. The level of eGFR was not associated with the level of cardiac output. Conclusions: Even mild kidney impairment is associated with higher systemic vascular resistance and increased supine sympathovagal balance. However, changes in autonomic tone, as based on analysis of heart rate variability, do not seem to explain the relation between lower eGFR and higher systemic vascular resistance in the upright position. The close relationship between the regulation of GFR and systemic vascular resistance may play a role in the pathogenesis of primary hypertension.